Sams teach yourself Drupal in 24 hours - Feiler, Jesse (Sams teach yourself in 24 hours series., 2010)
In just 24 sessions of one hour or less, learn how to build powerful, easy-to-maintain websites with Drupal-fast! Using this book's straightforward, step-by-step approach, you'll master every skill you'll need, from organizing sites and using Drupal's design themes to setting up search, polls, forums, and security. Each lesson builds on what you've already learned, giving you a rock-solid foundation for real-world success! Step-by-step instructions carefully walk you through the most common Drupal tasks. Quizzes and Exercises at the end of each chapter help you test your knowledge. By the Way notes present interesting information related to the discussion. Did You Know? tips offer advice or show you easier ways to perform tasks. Watch Out! cautions alert you to possible problems and give you advice on how to avoid them. Jesse Feiler provides consulting services to small businesses and non-profits through his company, North Country Consulting (northcountryconsulting.com). His recent books include FileMaker Pro 10 In Depth, The Bento Book, How to Do Everything with Web 2.0 Mashups, and iWork '09 For Dummies®. Register your book at informit.com/register for convenient access to all sample project source code, as well as updates and corrections as they become available. Category: Web Development Covers: Drupal User Level: Beginning--Intermediate Learn how to... Make the most of Drupal, whether you're building business, non-profit, or personal sites Download, install, and configure open source Drupal 6 and 7, and make sure it's working properly Plan and organize your sites so they are easy to manage-and friendly to both users and search engines Customize sites with Drupal's extensive library of optional open source modules Create barebone sites and home pages automatically Add text, images, links, and other essential site features Master Drupal's powerful Content Construction Kit (CCK) Incorporate new types of content, ranging from articles to e-commerce products Secure Drupal sites by managing users, permissions, roles, and user profiles Categorize and tag content, and implement full-text search Promote user involvement with polls, comments, forums, RSS feed aggregation, blogs, and newsletters Automate and simplify site management with Triggers, Actions, and Rules.